Integrating Mechanisms in Thrombotic Peripheral Arterial Disease - Magdolna Nagy; Paola E. J. van der Meijden; Julia Glunz; Leon Schurgers; Esther Lutgens; Hugo ten Cate; Stefan Heitmeier; Henri M. H. Spronk (MDPI AG, 2022)
Peripheral arterial disease (PAD), a manifestation of systemic atherosclerosis, is underdiagnosed in the general population. Despite the extensive research performed to unravel its pathophysiology, inadequate knowledge exists, thus preventing the development of new treatments. This review aims to highlight the essential elements of atherosclerosis contributing to the pathophysiology of PAD. Furthermore, emphasis will be placed on the role of thrombo-inflammation, with particular focus on platelet and coagulation activation as well as cell-cell interactions. Additional insight will be then discussed to reveal the contribution of hypercoagulability to the development of vascular diseases such as PAD. Lastly, the current antithrombotic treatments will be discussed, and light will be shed on promising new targets aiming to aid the development of new treatments.